Pendidikan Karakter sebagai Pendidikan Neurokognitif: Kajian Neurosains Spiritual dalam Pendidikan - Al Awwali, Sholihin; Suyadi, Suyadi (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research is to learn more about the function and role of the human brain. This research will focus on how the brain's ability to create and develop neuroscience-based character education can be used by educators, especially those working in the field of education.Method – In this descriptive research, researchers collect and analyze data to provide interpretations or explanations. The inductive method is used to identify patterns or themes from the collected data and then infer general findings. Deductive methods are used to apply existing theories or knowledge to understand the data or solve specific problems identified from the data.Findings – The brain plays an important role in individual character development, which is closely related to the brain's nervous system. Character education is an important component in Islamic education. This is because character education teaches values that can be applied in everyday life, such as honesty, responsibility, and empathy. There is a connection between the brain's nervous system and character development. Human character develops through the interaction and regulation of the nervous system in the brain. Six Major Nervous Systems in the Brain: Prefrontal Cortex, Limbic System, Gyrus Cingulatus, Basal Ganglia, Temporal Lobe, Cerebellum. Character education plays an important role in optimally developing the human brain. By teaching character values, character education helps in the regulation of behavior and the development of social and emotional skills that are important for everyday life. Research Implications – The implications of this research show that character education as brain education emphasizes the relationship between the brain and human character in relation to spiritual values in Islamic education. The importance of integrating between neuroscience and spirituality in education, to develop neuroscience-based character education that can be used by educators, especially those working in the field of education.